Streptococcus suis infection: a series of 41 cases from Chiang Mai University Hospital - Wangkaew S. (2014)
The objectives of this study were (1) to assess the clinical manifestations, treatment, and outcome of Streptococcus suis infection in adult patients in northern Thailand, (2) to evaluate the anti-microbial sensitivity pattern and (3) to determine the predicting factors of high mortality rate.